Brodsky’s coding method for propositional logic - Romas Alonderis (Lietuvos Matematikos Rinkinys, 2017)
Brodsky’s coding method for propositional logic is considered in the paper. Based on the sequent calculus, the method allows us to determine whether an arbitrary sequent is derivable in the calculus without constructing proof-search trees. The coding method, presented in the paper, can be used as a decision procedure for propositional logic.